Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is a practice problem for a midterm in a real analysis undergrad class, but I tagged it as homework anyway.

Suppose that $a_k>0$ and that the series $\sum_{k=1}^\infty a_k$ diverges. Let $S_n$ = $\sum_{k=1}^n a_k$ and define $b_1 = a_1$ and $b_n = \sqrt{S_n}-\sqrt{S_{n-1}}$ for $n\ge2$. Prove that $\sum_{k=1}^\infty b_k$ diverges, and that $\lim_{x\to\infty}\frac{b_n}{a_n}=0$. Conclude that there is no universal "smallest" comparison series to test divergence.

So $S_n = S_{n-1}+a_n$ and as n increases that $a_n$ will diverge. The square roots are messing me up, I don't know how to start with the limit and I understand the last statement, but I don't see how I can conclude it.

share|cite|improve this question
up vote 3 down vote accepted

To show that $\sum_{k=1}^\infty b_k$ diverges, you clearly have to look at the partial sums. As you might expect from the definition of $b_n$, it turns out that they telescope:

$$\begin{align*} &\sum_{k=1}^nb_k=a_1+\sum_{k=2}^nb_k=a_1+\sum_{k=2}^n(\sqrt{S_k}-\sqrt{S_{k-1}})=\\ &=a_1+\sum_{k=2}^n\sqrt{S_k}-\sum_{k=2}^n\sqrt{S_{k-1}}=a_1+\sum_{k=2}^n\sqrt{S_k}-\sum_{k=1}^{n-1}\sqrt{S_k}=\\ &=a_1+\sqrt{S_n}-\sqrt{S_1}=a_1+\sqrt{S_n}-\sqrt{a_1}\;. \end{align*}$$

Since $S_n\to\infty$ as $n\to\infty$, the same is true of the $\sqrt{S_n}$’s, and it follows that $\sum_{k=1}^\infty b_k$ diverges.

Now for $n\ge 2$ we have $$\begin{align*} \frac{b_n}{a_n}&=\frac{\sqrt{S_n}-\sqrt{S_{n-1}}}{a_n}\\ &=\frac{\sqrt{S_n}-\sqrt{S_{n-1}}}{a_n}\cdot\frac{\sqrt{S_n}+\sqrt{S_{n-1}}}{\sqrt{S_n}+\sqrt{S_{n-1}}}\\ &=\frac{S_n-S_{n-1}}{a_n(\sqrt{S_n}+\sqrt{S_{n-1}})}\\ &=\frac{a_n}{a_n(\sqrt{S_n}+\sqrt{S_{n-1}})}\\ &=\frac1{\sqrt{S_n}+\sqrt{S_{n-1}}}\;, \end{align*}$$

which clearly tends to $0$ as $n\to\infty$. (When you have a difference of square roots, it’s always worth thinking about this trick.)

Finally, the fact that $\frac{b_n}{a_n}$ tends to $0$ means that $\sum_{k=1}^\infty b_n$ is ‘smaller than’ $\sum_{k=1}^\infty a_n$, and yet it still diverges. That is, given a divergent series, you can always find a ‘smaller’ one, so there is no ‘smallest one’.

share|cite|improve this answer

These are some hints.

To prove that $\sum\limits_nb_n$ diverges, use the fact that $b_n=c_n-c_{n-1}$ for some sequence $(c_n)_n$ and express the partial sums $\sum\limits_{n\leqslant N}b_n$ in terms of $(c_n)_n$.

To prove that $b_n/a_n\to0$, rewrite $b_n$ as a ratio, multiplying and dividing $b_n$ by the conjugate quantity $\sqrt{S_n}+\sqrt{S_{n-1}}$.

The conclusion is that for every divergent series $\sum\limits_na_n$, there exists another divergent series $\sum\limits_nb_n$ such that $b_n=o(a_n)$, in this sense the latter is smaller than the former. In particular there exists no sequence $(t_n)_n$ such that $\sum\limits_na_n$ diverges if and only if $a_n=\Omega(t_n)$.

share|cite|improve this answer
+1 Everything was simple but the first step, I definitely overcomplicated it. – Ilya Nov 17 '11 at 10:38

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.